토픽 모델링과 의미망 분석을 활용한 땅밀림 관련 뉴스 기사와 연구 논문의 동향 분석 - 윤상후; Sanghoo Yoon; 곽민서; Minseo Kwak; 김동엽; Dongyeob Kim (한국산림과학회지, 2025)
기후변화로 인한 자연재해 발생 빈도가 증가함에 따라 땅밀림 현상이 사회적 그리고 학문적 관심을 받고 있다. 본 연구는 2004년부터 2024년까지 수집된 뉴스 기사와 연구 논문의 텍스트 데이터를 대상으로 텍스트 마이닝 기법, 특히 토픽모델링과 의미망 분석을 적용하여 땅밀림과 관련된 주요 이슈와 연구 동향을 분석하였다. 뉴스 기사 분석에서는 주로 지역사회의 대응 노력, 정부 정책, 기술 도입이 강조된 반면, 연구 논문 분석에서는 땅밀림의 지질학적 특성, 예측 모델, 첨단기술 활용 방안이 중심이 되었다. 두 데이터는 모두 예방적 접근의 중요성을 공유하며, 뉴스 기사는 실질적 사례를, 연구 논문은 이론적 기초와 기술적 해결책을 제시한다. 본 연구의 결과는 땅밀림 관련 연구의 초기 단계에서의 학문적 공백을 메우고, 향후 연구 및 정책 방향에 중요한 통찰을 제공할 것으로 기대되었다. As the frequency of natural disasters caused by climate change increases, academics and the general public alike have become increasingly concerned with landcreep phenomena. This study applies text mining techniques, particularly topic modeling and semantic network analysis, to text data collected from news articles and research abstracts published between 1995 and 2024. The analysis of news articles highlights community response efforts, government policies, and technology adoption, whereas the research abstracts focus on the geological characteristics of landcreeps, prediction models, and the application of advanced technologies. Both the practical cases in the news articles and the theoretical foundations and technical solutions in the research papers emphasize the importance of a preventive approach. This study addresses an academic gap in the early stages of landcreep research and provides important insights for future research and policy directions.